TINDAK KOMUNIKASI SUMBER DAYA MANUSIA TUNARUNGU - Zera Edenzwo Subandi; Celline Febianca (Ikon --Jurnal Ilmiah Ilmu Komunikasi, 2022)
This research was conducted to determine the process of interaction between deaf people and people heard at Sunyi House of Coffee and Hope through the perspective of Communication Psychology. In the interaction of both, there is a mirror neuron process that explains that humans create motor templates - a prototype or blueprint in the brain - that allows humans to mimic certain movements or certain tones in response to the other person. This research is a qualitative research using a case study method with the source of data analysis taken from observations, interviews and documentation. Therefore, the researcher uses data triangulation and exploration data analysis techniques. The results of the study found that mirror neurons are very helpful between deaf and non-deaf people in an attempt to encode and decode messages between communicators and communicants through imitation of movement as part of the response to the interlocutor. In addition it is evident that the five parts of the body that are discussed in mirror neurons, namely the lips, neck, shoulders, hands, and feet have a major role in the communication process of fellow deaf people. Based on observations on deaf baristas, researchers believe that deaf human resources can compete with non-deaf human resources in the country so that companies need to provide equal opportunities for deaf human resources to work.